Safety of endoscopic retrograde cholangiopancreatography in the pediatric population: a multicenter study - Mercier, Clémence; Pioche, Mathieu; Albuisson, Eliane; Ponchon, Thierry; Gonzalez, Jean-Michel; Barthet, Marc; Boytchev, Isabelle; Vanbiervliet, Geoffroy; Fortier Beaulieu, Clement; Prat, Frederic; Belle, Arthur; Branche, Julien; Grandval, Phillipe; Valats, Jean-Christophe; Rudler, Franz; Wallenhorst, Timothee; Koch, Stephane; Comte, Aurélie; Williet, Nicolas; Musquer, Nicolas; Coron, Emmanuel; Derosiere, Aline; Le Mouel, Jean-Phillippe; Schaefer, Marion; Chabot, Caroline; Scheers, Isabelle; Deprez, Pierre H.; Chevaux, Jean-Baptiste (Endoscopy, 2020)
Introduction The aims of this retrospective multicenter study were to assess the technical success and adverse events of endoscopic retrograde cholangiopancreatography (ERCP) procedures in children in French and Belgian centers.Methods All children aged 1 day to 17 years who underwent ERCP between January 2008 and March 2019 in 15 tertiary care hospitals were retrospectively included.Results 271 children underwent 470 ERCP procedures. Clinical long-term follow-up was available for 72 % of our patients (340/470 procedures). The median age at intervention was 10.9 years. ERCP was therapeutic in 90 % (423/470) and diagnostic in cases of neonatal cholestasis in 10 % of the patients. The most common biliary indication was choledocholithiasis; the most common pancreatic indication was chronic pancreatitis. Biliary cannulation was successful in 92 % of cases (270/294); pancreatic cannulation in 96 % of cases (169/176); and planned therapeutic procedures in 92 % of cases (388/423). The overall complication rate was 19 % (65/340). The most common complication was post-ERCP pancreatitis (PEP) in 12 % of cases (40/340) and sepsis in 5 % (18/340). On univariate analyses, pancreatic stent removal was protective against PEP (odds ratio [OR] 0.1, 95 % confidence interval [CI] 0.01 – 0.75; P = 0.03), and sepsis was associated with history of liver transplantation (OR 7.27, 95 %CI 1.7 – 31.05; P = 0.01). Five patients had post-ERCP hemorrhage and two had intestinal perforation. All complications were managed with supportive medical care. There was no procedure-related mortality. Conclusion Our cohort demonstrates that ERCP can be performed safely with high success rates in many pancreaticobiliary diseases of children. The rate of adverse events was similar to that in previous reports.